2016
DOI: 10.1097/adt.0000000000000075
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity and Smoking Variability Among Treatment Seeking Smokers

Abstract: Objectives Anxiety sensitivity (AS) is associated with poor smoking cessation outcomes. One reason may be that smokers with high AS smoke differently (i.e., to manage negative affect and uncomfortable bodily sensations) than other smokers, leading to stronger addiction (due to an affect/sensation based and thereby highly variable rather than a regular smoking routine). Thus, we examined the relationship between AS and smoking variability in a group of treatment-seeking smokers. Methods Participants (N = 136;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Higher anxiety sensitivity has been associated with increased lower respiratory symptoms and a greater risk of smoking relapse [33]. Smokers with respiratory symptoms who had heightened anxiety sensitivity were also more emotionally susceptible to somatic sensations and life stressors, which was possibly due to a dysfunctional cognitive–affective reaction to threatening situations [34], thereby contributing to negatively reinforced behavior such as continued smoking. The second interpretation is that respiratory symptoms cause or contribute to anxiety symptoms, and many studies have also supported this direction of the causality of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Higher anxiety sensitivity has been associated with increased lower respiratory symptoms and a greater risk of smoking relapse [33]. Smokers with respiratory symptoms who had heightened anxiety sensitivity were also more emotionally susceptible to somatic sensations and life stressors, which was possibly due to a dysfunctional cognitive–affective reaction to threatening situations [34], thereby contributing to negatively reinforced behavior such as continued smoking. The second interpretation is that respiratory symptoms cause or contribute to anxiety symptoms, and many studies have also supported this direction of the causality of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…paper. Studies have shown that individuals with anxiety disorders have higher nicotine dependence, more severe withdrawal symptoms, and experience greater cessation fatigue (i.e., being tired of making attempts to quit smoking) as compared to those without anxiety (Morissette, Tull, Gulliver, Kamholz, & Zimering, ; Powers et al., ; Tidey & Miller, ). In addition, the fact that our study sample provided self‐reports of their anxiety disorder diagnosis may affect the comparability of our results to those of other findings using standardized clinical interview schedules to define anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…pharmacological and psychosocial treatment; Zvolensky, Stewart, Vujanovic, Gavric, & Steeves, 2009) and unaided quit attempts (i.e., self-guided quit attempt; Marshall, Johnson, Bergman, Gibson, & Zvolensky, 2009). Other studies demonstrate that AS mediates the relation between emotional disorders and severity of smoking behavior (Olvera et al, 2015; Powers et al, in press; Zvolensky, Farris, Leventhal, & Schmidt, 2014; Zvolensky et al, in press). Importantly, smokers respond to AS reduction treatment after a single intervention session (Feldner, Zvolensky, Babson, Leen-Feldner, & Schmidt, 2008).…”
mentioning
confidence: 93%